2008
DOI: 10.1002/jhm.340
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence in women hospitalized on an internal medicine service: Prevalence and relationship to responses to the review of systems

Abstract: BACKGROUND:Although intimate partner violence is common, the prevalence in patients hospitalized on internal medicine services and whether it is associated with numerous positive responses to the review of systems are not known.OBJECTIVE:The objective of this study was to assess the prevalence of intimate partner violence in women hospitalized on an internal medicine service and to determine whether it is associated with the number or types of positive responses to the review of systems.DESIGN:This was a prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“… 33 35 Indeed, several studies have reported that patients who have a history of adverse childhood experiences or post-traumatic stress disorder or are victims of intimate partner violence often have multiple somatic complaints and an increased prevalence of both functional and chronic illnesses. 36 44 …”
Section: Co-morbid Psychiatric Disorders and Traumamentioning
confidence: 99%
“… 33 35 Indeed, several studies have reported that patients who have a history of adverse childhood experiences or post-traumatic stress disorder or are victims of intimate partner violence often have multiple somatic complaints and an increased prevalence of both functional and chronic illnesses. 36 44 …”
Section: Co-morbid Psychiatric Disorders and Traumamentioning
confidence: 99%
“…A recent systematic review of 37 published papers on IPV prevalence in health care settings found that the pooled lifetime prevalence of IPV was 38 % in family medicine and 40 % in emergency medicine [1]. Previous studies have found that 13-27 % of women have experienced IPV in the past year [6][7][8][9][10][11]. The studies, however, are primarily from the United States and focused on Caucasian, African American, and Latina populations [1].…”
Section: Introductionmentioning
confidence: 97%
“…The relationship between IPV and mental health problems has been well-documented with depression, dysthymia, suicidality, generalized anxiety disorder, phobias, and posttraumatic stress disorder (PTSD) all associated with the experience of IPV (10–15). Some studies reported worse outcomes associated with greater frequency and severity of IPV (16), whereas others reported that even so-called low levels of violence (such as pushing or shoving) are associated with depression (17, 18).…”
mentioning
confidence: 99%